Vector error correction heterogeneous autoregressive forecast model of realized volatility and implied volatility. Issue 5 (28th May 2019) - Shin, Ji Won; Shin, Dong Wan
ABSTRACT: A vector error correction model is proposed for forecasting realized volatility which takes advantage of the cointegration relation between realized volatility and implied volatility. The model is constructed by adding a cointegration error term to a vector-and-unit-root version of the heterogeneous autoregressive (HAR) model of Corsi (2009 ). The proposed model is easier to implement, extend, and interpret than fractional cointegration models. A Monte Carlo simulation and real data analysis reveal advantages of the proposed model over other existing models of Corsi (2009 ), Busch Christensen and Nielsen (2011 ), Cho and Shin (2016 ), and Bollerslev Patton, and Quaedvlieg (2016 ).